Nontoni in the Tradition of the Javanese Muslim Society, Kperabon Perspective of Madzhab Shafi'I and the Anthropology of Islamic Law - Abduloh Rohman Utomo; Fadil; Isroqunnajah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Academic concern regarding the nontoni tradition stems from the tension between local cultural practices and the normative principles of Islamic law governing interactions between unmarried men and women. Practiced within the Muslim Javanese Keprabon community, nontoni remains an important stage in the spouse selection process while raising questions concerning its Sharīʿah legitimacy and its accommodation within Islamic legal discourse. This study aims to examine the implementation, social meaning, and legal implications of the nontoni tradition in Tulus Village, Tumpang District, Malang Regency, through the perspective of Islamic legal anthropology. The research employs an empirical qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving community leaders, religious figures, practitioners of the tradition, and local residents. Data analysis was conducted descriptively using the concepts of ʿurf, maṣlaḥah, relevant legal maxims (qawāʿid fiqhiyyah), and Islamic legal anthropology. The findings reveal that nontoni serves not only as a process of observing a prospective spouse but also as a cultural institution that facilitates mutual acquaintance, family deliberation, and social legitimation before marriage. From the perspective of Islamic legal anthropology, the tradition represents a dynamic form of ʿurf ṣaḥīḥ that remains compatible with Islamic law, provided it preserves ethical boundaries, avoids prohibited conduct, and supports the objectives of maqāṣid al-sharīʿah. The study demonstrates that local customs can coexist with Islamic legal principles through a contextual and culturally sensitive interpretation.